Why is it important to detect atrophic gastritis and gastric intestinal metaplasia? What is the proper way to do it? - Sarem, Muhannad (2020)
Gastric intestinal metaplasia and atrophic gastritis are a known recancerous condition (PCC) of the stomach, meaning that patients with PCC are at risk for gastric cancer and so, diagnosis and risk categorization for these patients is relevant. The aim of this review is to provide an update regarding the problem, diagnosis, and management of PCCs with an emphasis on the role of appropriate endoscopic detection.